HUBUNGAN TINGKAT SPIRITUAL DENGAN KECEMASAN MAHASISWA TINGKAT AKHIR DALAM MENYUSUN SKRIPSI - Mhd. Ikhwan Nulhakim; Febriana Sabrian; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Spiritual can increase immune system physically or mentally, and anxiety in students can be prevented by upgrading their spiritual level. The purpose of this study was to determine the relationship of spiritual levels and anxiety of final grade students in completing thesis. The design of this study was descriptive correlation with cross-sectional approach. This research was conducted at Faculty of Nursing University of Riau with 115 respondents that were taken based on inclusion criteria using total sampling technique. The research instrument used were questionnaires that have been tested by validity and realibility test. Data was analyzed by univariate analysis to determine the frequency distribution and bivariate analysis with chi-square test. The results of this study showed that there were 49 respondents who had moderate spiritual level with low anxiety level (42, 6%). According to bivariate test analysis there was no significant relationship between the spiritual level and the anxiety of final grade students in completing that thesis with p value (0.119) > α (0.05). So that it can be concluded that there was no colleration between spiritual level and the anxiety of the final level students in preparing the thesis. Based on the result, it is suggested that students may improve their spirituality level and reduce anxiety when preparing a thesis. Keywords: Anxiety, Spiritual, Students